Behavioural economics and policy design examples from Singapore - Low, Donald, 1973- (World Scientific, 2012)
"This book aims to demonstrate how successful policies in Singapore have integrated conventional economic principles with insights from the emerging field of behavioural economics even before the latter became popular. Using examples from various policy domains, it shows how good policy design often requires a synthesis of insights from economics and psychology. Policies should not only be compatible with economic incentives, but should also be sensitive to the cognitive abilities, limitations and biases of citizens. Written by policy practitioners in the Singapore government, this book is an introduction to how behavioural economics and the findings from cognitive psychology can be intelligently applied to the design of public policies."--Publisher's description.